Evaluation of mahua oilcake (Bassia latifolia Roxb.) as a non-conventional feed ingredient for Labeo rohita (Ham.) fingerlings - Rath, S. C.; Nayak, K. C.; Mohanty, T. K.; Devraj, C.; Chandan, N. K.; Mohanta, K. N.; Giri, S. S. (Indian Journal of Fisheries, 2017)
Mahua (Bassia latifolia Roxb.) oil cake (MOC) is rich in protein (24%) and energy (19.0 KJ g-1) with high levels of fatty acids comprising saturates (45%), monoenes (42%) and polyunsaturated fatty acids (PUFA, n-6) (7%). Saponin, phenol and flavonoids are the main metabolites. Labeo rohita (Hamilton, 1822) fingerlings (5.25Â±0.2 g) were fed with five iso-nitrogenous (28% CP) diets containing MOC at 0% (F1), 10% (F2), 20% (F3), 30% (F4) and 40% (F5) for 90 days in 300 l cement cisterns. Survival (%) of all groups were statistically similar (p>0.05). Weight gain (%) and specific growth rate (SGR) were significantly lower in F1, F2, F5 and higher in F3 and F4 groups (p<0.05). Feed conversion ratio (FCR) was significantly lower (p<0.05) in F4 as compared to the other groups. Among all the dietary treatments, significantly higher (p<0.05) protein efficiency ratio (PER) and net protein utilisation (NPU) were found in F4. Whole body protein and lipid was significantly higher (p<0.05) in F4 and F3, respectively. Hemoglobin, glucose, protein and cholesterol in blood were found to be at higher levels in F4 group. All these parameters declined, but serum glutamic oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) levels increased significantly (p<0.05) in F5. The findings of the study clearly indicated that MOC can be incorporated at 300 g kg-1 in the diet of L. rohita fingerlings without any adverse effect on growth, survival and nutrient utilisation.